Contribution to the study of Bartonella Muris - Battistini, T. (1926)
In 1921 E. Mayer Tropical Institute in Hamburg, studying the action of "Bayer 0205" on rats experimentally infected with Trypanosoma rhodesiense, the presence of elements found in red blood cells, whose morphology judged quite similar to that of the etiologic agent Bartonella bacilliformis Peruvian wart.